Chloride penetration in cracked mortar and the influence of autogenous crack healing. (15th July 2016) - Maes, Mathias; Snoeck, Didier; De Belie, Nele
Highlights: Autogenous crack healing of mortar exposed to marine environments is investigated. Mortars are able to autogenously heal or seal crack widths up to 100 μm. Crack sealing is also obtained by formation of a brucite layer at the surface. The resistance against chloride penetration improves due to the healing process. 10 μm is the critical crack width for chloride penetration. Abstract: Cracks in cementitious materials have a negative influence on the durability in aggressive environments, especially in marine environments since chlorides and sulphates are able to penetrate faster. Since constructions in marine environments mostly have an important social function with a high economic impact, repair of the cracks is of utmost importance. In this paper, the ability of the material to heal 100 μm and 300 μm cracks autogenously in marine environments is investigated. To do so, some Ordinary Portland Cement mortar samples and Blast-furnace Slag blended mortar samples were permanently immersed in chloride solutions as well as in combined chloride and sulphate solutions. Another part of the samples were exposed to wet-dry cycles in water and in chloride solutions. Autogenous crack healing was evaluated by means of microscopic measurements. The resistance against chloride penetration was measured by means of colorimetric measurements and chloride profiles. It was shown that cementitious materials, exposed to a simulated marine environment, are able to heal or seal crack widths up to 100 μm. Autogenous healing is obtained by ongoing hydration, calcium carbonate precipitation as well as by formation of a layer of magnesium and sulphate reaction products (brucite) at the surface. Furthermore, the resistance against chloride penetration improves due to the healing process. However, the efficiency depends on the initial crack width.